1995
DOI: 10.1007/bf02211378
|View full text |Cite
|
Sign up to set email alerts
|

Increased incidence of aberrant morphological phenotypes in human embryogenesis—An association with endometriosis

Abstract: The incidence of defined aberrant phenotypes in embryos from women with laparoscopically documented endometriosis may allow us to identify specific embryotoxic events with reference to endometriosis and other diagnoses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
47
0
11

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(63 citation statements)
references
References 12 publications
5
47
0
11
Order By: Relevance
“…Other benign diseases, such as recurrent ovarian endometriosis or recurrent ovarian mucinous cysts, are also indications for OTC, even if these indications have become questionable in the light of recent studies. Severe endometriosis is known to be associated with decreased oocyte quality [6] and lower serum antiMüllerian hormone (AMH) concentrations [55]. This corroborates one of our studies in which endometriotic ovarian cysts were described as a possible cause of reduced ovarian reserve in women with endometriosis [29].…”
Section: Incidence Of Indications and Comparison With Other Reportssupporting
confidence: 86%
“…Other benign diseases, such as recurrent ovarian endometriosis or recurrent ovarian mucinous cysts, are also indications for OTC, even if these indications have become questionable in the light of recent studies. Severe endometriosis is known to be associated with decreased oocyte quality [6] and lower serum antiMüllerian hormone (AMH) concentrations [55]. This corroborates one of our studies in which endometriotic ovarian cysts were described as a possible cause of reduced ovarian reserve in women with endometriosis [29].…”
Section: Incidence Of Indications and Comparison With Other Reportssupporting
confidence: 86%
“…Despite the fact that oocyte-retrieved count and fertilization rate were similar in both endometriosis and control groups of the present study, there was a substantial difference in the number of high-and low-quality embryos between groups (Table 2). This is consistent with other studies that showed a significant increase in the percentage of arrested embryos and aberrant zygote formation in patients with endometriosis compared with control group [49,55]. Indeed, our clinical analysis revealed that women with endometriosis required higher dosage of gonadotropins during ovarian stimulation (Table 2).…”
Section: Discussionsupporting
confidence: 92%
“…Indeed, a previous study found microtubule and chromosomal changes in poor quality oocytes, which could potentially explain the reduced fertilization rates, as well as reduced implantation rates [2]. Furthermore, a direct correlation between the disease and prevalence of nuclear and cytoplasmic aberrations was observed in pre-implantation embryos obtained from women undergoing IVF cycles for endometriosis-associated infertility [29]. Another possible mechanism involves the effect of follicular fluid (FF) on gamete interaction.…”
Section: Discussionmentioning
confidence: 99%